Study on the Removal Efficiency and Mechanism of Tetracycline in Water Using Biochar and Magnetic Biochar - Hongwei Sun (MDPI AG, 2021)
In this study, a new type of sludge-derived biochar material with high tetracycline removal efficiency, named magnetic Fe3O4 biochar, was accomplished by KOH activated and loaded with magnetic Fe3O4. The particles with spherical pellets observed by SEM, as well as the XRD patterns, indicated that magnetic Fe3O4 nanoparticles were successfully loaded onto the biochar. We studied the adsorption effects and mechanisms of the following three different adsorption materials for tetracycline: biochar (BC), magnetic Fe3O4, and magnetic biochar (MBC), and the loading conditions and reusability of the materials were also considered. The adsorption effects were as follows: Fe3O4 (94.3%) > MBC (88.3%) > BC (65.7%), and the ratio of biochar to ferric salt was 0.2:1; the removal effect reached the best result. Under an acidic condition, the adsorption capacity of all the materials reached the maximum, and the adsorption of tetracycline in water, by three adsorbents, involves chemical adsorption as the leading process and physical adsorption as the auxiliary process. Various characterizations indicated the removal of tetracycline, including pore filling, electrostatic interaction, hydrogen bond action, and cationic-π action. Complex bridging is a unique adsorption mechanism of magnetic Fe3O4 and magnetic biochar. In addition, the magnetic biochar also possesses π–π bond interaction. The magnetic materials can still maintain a certain amount of adsorption capacity on tetracycline after five cycles. This study proved that the magnetic sludge-based biochar are ideal adsorbents for the removal of tetracycline from water, as well as an effective route for the reclamation of waste sludge.